PENGARUH PENERAPAN DISCHARD PLANNING PERAWAT TERHADAP PENGETAHUAN PENGELOLAAN NUTRISI PADA PASIEN DIABETES MELITUS TIPE 2 DI RUANG RAWAT INAP RSUD PROF DR.H. ALOE SABOE KOTA GORONTALO - Pipin Yunus; Haslinda Damansyah (-, 2021)
This study is to investigate discard planning performed by the nurses with capability in organizing nutrition to diabetes type II patients. The design used is pre-experimental study with one group pre and post test design. The sample is 10 patients. The data is analyzed by using paired t test. The result shows that there is a significant relationship of discard planning performed by nurses with their capability in organizing nutrition to diabetes type II patients with value 0.000 ka= 0.05). it is suggested that the nurses should give discard planning treatment comprehensively to the patients before they go home.